Radio Frequency Study of S-band Side Coupled Accelerating Structure - Aleem, M. A.; Khan, M. A.; Khalid, R.; Mahmood, I. (The Nucleus, 2021)
Currently, PINSTECH is developing S-band electron linear accelerator (LINAC) for medical applications. The side coupled accelerating structure (SCAS) was selected for electron acceleration process in the LINAC due to its compactness and high efficiency. The basic concept of SCAS was derived from the design of biperiodic chain of coupled cavities already published in the literature. This study focuses on the conceptual design realization and optimization of the structure through radio frequency (RF) simulations. COMSOL electromagnetic solver was used for the RF simulation work. The working frequency and excitation mode were selected as 2998 MHz and Ï€/2, respectively. The design process of SCAS is stepwise explained starting from unit section to the complete stack of unit sections. The coupling iris was optimized to transfer maximum RF power to the structure. The electric field profile on the axis of SCAS was successfully optimized to achieve the field flatness. Subsequently, the characteristic parameters were derived directly through post processing of the simulation results.